Association between Hypotension, Low Ejection Fraction and Cognitive Performance in Cardiac Patients - Rebecca F. Gottesman; Maura A. Grega; Maryanne M. Bailey; Scott L. Zeger; William A. Baumgartner; Guy M. McKhann; Ola A. Selnes (Behavioural Neurology)
Background and Purpose: Impaired cardiac function can adversely affect the brain via decreased perfusion. The purpose of this study was to determine if cardiac ejection fraction (EF) is associated with cognitive performance, and whether this is modified by low blood pressure.